Estimation of Genetic Variability, Heritability and Genetic Advance for Seed Yield and Its Attributes in Sesame (Sesamum indicum L.) - Kadvani, Gopal; Patel, J. A.; Patel, J. R.; Prajapati, K. P.; Patel, P. J. (International Journal of Bio-resource and Stress Management, 2020)
The field experiment was conducted during July to October, 2018 at Castor-Mustard Research Station, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar, Gujarat, India to access genetic variability, heritability and genetic advance for seed yield and its attributing traits in 45 genotypes of sesame. Analysis of variance revealed significant difference among genotypes for all the eleven characters which indicated presence of sufficient variability among the genotypes under study, hence there is an ample scope of selection for superior and desired genotypes to plant breeder for further crop improvement. The values of phenotypic coefficient of variation were slightly higher than that of genotypic coefficient of variation for all the traits studied. The high values of genotypic coefficient of variation and phenotypic coefficient of variation were recorded for seed yield plant-1, leaf area plant-1 and number of effective branches plant-1 indicated the presence of wide genetic variation for these characters. High heritability was recorded for 1000 seed weight, followed by leaf area plant-1, oil content, days to flowering, capsule length plant-1, number of capsules plant-1, days to maturity, seed yield plant-1 and number of effective branches plant-1 indicated that heritability may be due to higher contribution of genotypic component in these traits. High heritability combined with high genetic advance as percentage of mean was recorded for leaf area plant-1, seed yield plant-1, number of effective branches plant-1, number of capsules plant-1, 1000 seed weight and days to flowering indicating that these characters are controlled by additive gene effect and phenotypic selection of these characters would be effective for genetic improvement of seed yield in sesame.